Analyse De Quelques Parametres De Consommation De Wavé-Fortex, Un Complement Alimentaire Naturel Du Gabon - Lepengue, Alexis Nicaise; Yala, Jean Fabrice; Souza, Alain; Mbatchi, Bertrand (European Scientific Journal, ESJ, 2018)
Wavé-fortex is a food supplement developed by Masuku University of Science and Technology (USTM) in Gabon. It aims at fighting against metabolic diseases, especially impotence, fatigue and sexual weakness, hypertension, overweight and cardiac arrhythmias. This study was conducted in order to analyze the distribution of consumption by type of diseases. The results revealed that Wavé-fortex is mainly consumed for problems of sexual dysfunction (41%), general fatigue (20%) and hypertension (15%). In terms of gender, men are the main consumers at 73%. Their consumption is mainly due to sexual stability concerns (51%), general fatigue (24%) and hypertension (23%). Among women, the concerns are rather overweight (32%) and hypertension (29%), before sexual disorders (21%). Wavé-fortex is a product mainly consumed in Gabon (70%), Congo (14%), Cameroon (6%) and France (2.5%), by patients aged between 30 and 70 years.